Evolving Information in an ‘Evidence-Based’ World: Theoretical Considerations - Genius, Shelagh K (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This literature-based critical analysis focuses on evidence-based practice and knowledge translation theory, particularly the Promoting Action on Research Implementation in Health Services (PARIHS) framework. Perspectives that facilitate exploration of factors influencing information behaviour in situations of uncertain and/or evolving health information are investigated. A medical case study provides context for this study. Cette analyse critique basée sur la littérature concerne la pratique fondée sur des preuves et la théorie de l’application des connaissances, en particulier la promotion de la mise en œuvre de la recherche dans le cadre des services de santé. Les points de vue facilitant l’exploration des facteurs ayant une incidence sur le comportement informationnel en situation d’information médicale incertaine ou en cours d’évolution sont examinés. Une étude de cas médical propose un contexte à cette recherche. ***Student to CAIS/ACSI Award Winner***